2018
DOI: 10.1111/joic.12522
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐free versus permanent polymer‐coated drug eluting stents for the treatment of coronary artery disease: A meta‐analysis of randomized trials

Abstract: PF-DES are as safe and efficacious as PP-DES for the treatment of patients with CAD, but do not significantly reduce late ischemic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…This recent paper of more extensive randomized clinical trials allows us to conduct the current meta-analysis, which compares PF-DES to PC-DES, including PP and BP-DES. We discovered that patients who received the new stents had a reduced all-cause mortality rate, similar to what Nogic et al [ 45 ] discovered. However, this increase in survival was not due to a reduction in recurring ischemic episodes or cardiovascular deaths.…”
Section: Reviewsupporting
confidence: 86%
See 1 more Smart Citation
“…This recent paper of more extensive randomized clinical trials allows us to conduct the current meta-analysis, which compares PF-DES to PC-DES, including PP and BP-DES. We discovered that patients who received the new stents had a reduced all-cause mortality rate, similar to what Nogic et al [ 45 ] discovered. However, this increase in survival was not due to a reduction in recurring ischemic episodes or cardiovascular deaths.…”
Section: Reviewsupporting
confidence: 86%
“…In particular, 1% of patients developed stent thrombosis, which could be attributed to the inclusion of a low-risk community of stable patients with confined outgrowths of cardiovascular problems. The vast majority of trials were underwhelming in assessing actual result metrics, and the greatest benefits of PF-DES were confirmed in trials encompassing subgroups of patients at greater risk [ 44 , 45 ].…”
Section: Reviewmentioning
confidence: 99%
“…Specifically, over half of the patients included in the analysis were recruited in trials published before 2013 utilizing older generation stents, which have shown inferior results to newer generation stents. Additionally, different stent polymer coating strategies have shown different clinical outcomes 9,10 . In contrast to our study, given the localized nature of VCOR and government and private contractual arrangements, although not specified in the registry there were only limited DES available all of which were second generation.…”
Section: Discussionmentioning
confidence: 67%
“…Additionally, different stent polymer coating strategies have shown different clinical outcomes. 9,10 In contrast to our study, given the localized nature of VCOR and government and private contractual arrangements, although not specified in the registry there were only limited DES available all of which were second generation. Given the low event rates, more recently published data, including ours and the utilization of newer DES generations, repeat meta-analysis of current data should be attempted to assess this hypothesis further.…”
Section: Discussionmentioning
confidence: 72%
“…Clinical outcomes following revascularization with percutaneous coronary intervention (PCI) have improved significantly over the last three decades, driven by advances in stent design, improved PCI techniques, and enhanced adjuvant pharmacotherapies [1,2]. However, recurrent cardiovascular events remain an ongoing clinical concern, with around half of these either attributable to the previously stented segment or residual disease located within the target vessel [3].…”
Section: Introductionmentioning
confidence: 99%